Impacts of flood on the lives and livelyhoods of people in Bangladesh: A case study of a village in Manikganj district - Rahman, Saleh Ur (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2014.